(untitled) (Olhar de Professor, 2024)
This review of the book entitled “Fundamentals of Historical-Critical Didactics”, was prepared in the context of the production of the 3rd Cycle of Studies at the Instituto Federal Goiano-Ceres, in partnership with the Federal Universities of RJ, Catalão and Goias (UNIRIO, UFCat and UFG). Organized by Galvão, Lavoura and Martins (2019), this work represents a robust synthesis of theoretical-practical assumptions that make it possible to understand the organization of teaching work in the light of Historical-Critical Pedagogy and Marxism and reveals to us that the Historical-Critical Didactics is that which identifies social practice as a starting and ending point, because through the movement from syncresis to synthesis, each singular individual can effectively incorporate the cultural instruments of human universality as a process of catharsis. To this end, it considers the mediating elements in the particular activity of pedagogical action – the action of problematization and instrumentalization.